Exploring the Link between Visual Perception, Visual–Motor Integration, and Reading in Normal Developing and Impaired Children using DTVP‐2. (10th July 2017) - Bellocchi, Stéphanie; Muneaux, Mathilde; Huau, Andréa; Lévêque, Yohana; Jover, Marianne; Ducrot, Stéphanie
Abstract : Reading is known to be primarily a linguistic task. However, to successfully decode written words, children also need to develop good visual‐perception skills. Furthermore, motor skills are implicated in letter recognition and reading acquisition. Three studies have been designed to determine the link between reading, visual perception, and visual–motor integration using the Developmental Test of Visual Perception version 2 (DTVP‐2). Study 1 tests how visual perception and visual–motor integration in kindergarten predict reading outcomes in Grade 1, in typical developing children. Study 2 is aimed at finding out if these skills can be seen as clinical markers in dyslexic children (DD). Study 3 determines if visual–motor integration and motor‐reduced visual perception can distinguish DD children according to whether they exhibit or not developmental coordination disorder (DCD). Results showed that phonological awareness and visual–motor integration predicted reading outcomes one year later. DTVP‐2 demonstrated similarities and differences in visual–motor integration and motor‐reduced visual perception between children with DD, DCD, and both of these deficits. DTVP‐2 is a suitable tool to investigate links between visual perception, visual–motor integration and reading, and to differentiate cognitive profiles of children with developmental disabilities (i.e. DD, DCD, and comorbid children). Copyright © 2017 John Wiley & Sons, Ltd.